A premature infant with Brucella abortus infection - Oran, Olcay; Karslıoğlu, Ahmet; Seçmeer, Gülten; Berkman, Erdoğan; Kanra, Güler (The Turkish Journal of Pediatrics, 1983)
A case of Brucella abortus in a premature neonate with a septic condition. The relationship between this infection and the early delivery is investigated and the relevant literature reviewed.
Keywords: Brucella infection; premature baby; sepsis